Planning for the Next Wave: Assessing Current Faculty Distance Education Training and Development Needs - Tracy Irani; Ricky Telg (Journal of Applied Communications, 2001)
As part of a strategic effort to enhance support services for faculty engaged in distance education, a descriptive study was conducted to assess the perceived distance education training and development needs of faculty members at a southern region land-grant university. Results of the study indicated that those who responded felt distance education training should be conducted in a traditional format, such as a prescribed course or set of training materials, and that the best I· format would be self-paced training or a combination of formal, informal, and self-paced training. Respondents were almost evenly split on whether training should be mandatory or voluntary for faculty teaching distance education courses.